Overview of Indian Economy with its Recent Development: Examining the Best Performing Sectors and the Impact of GST in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India's balanced economy includes conventional village farming, contemporary forestry, crafts, a broad variety of modern industries, multitude of services. India is evolving into an open-market economy, but remnants of its previous autochthonous policies exist. Economic liberalization initiatives, including market reform, privatization of state-owned companies and relaxed restrictions on foreign trade investment, started at the beginning of the 1990s. In this article, we will review the analysis of the best performing sectors of the Indian economy and the impact of GST on the Indian economy.